Validitas Pemeriksaan Radiografi Bite-Wing Pada Karies Sekunder Restor; Amalgam - Adam Malik Hamudeng; Asdar Gani (DiscoverSys Inc., 2007)
Secondary caries is one of cause the importance of commutation ofamalgam restoration. The ; existence of sekunder karies can be detectwith visual method and tactile sensation with sonde, but this notapplicable if the lesion is small or not seen. The difficulty to detect thislesion can be done through bite-wing radiography to support thediagnosis. Rudolphy 1 describe that at large and medium cavity willseen radio-lusen at inspection of radiography, while for small cavity will seen the image of radio-opasitas. Result of prospective study indicatethat grey discolouration have 50% sensitifity and 91% spesifity indetecting secondary caries.